Efficacy of low-dose versus conventional-dose bupivacaine in spinal anesthesia induction: A narrative review article - Amir Sabertanha; Samaneh Kouzegaran; Ramin Honarmand; Sajjad Jahangiri (Reviews in Clinical Medicine, 2023)
Spinal anesthesia is gaining popularity and more frequent use due to its efficacy, patient satisfaction, lower complication rates, and good durability. Nerve blocks reduce the complications and risks associated with general anesthesia and lessen the patient’s need for postoperative care compared to general anesthesia, leading to earlier patient discharge. One spinal procedure involves administering low doses for anesthesia induction. This review article explored this approach by incorporating studies reporting the administration of lower doses of the local anesthetic bupivacaine. Findings indicate that lower and conventional doses of bupivacaine have comparable sensory and motor block impacts and induction times. However, the recovery time at lower doses is faster, and patients are discharged sooner from the postanaesthetic care unit. Complications associated with spinal anesthesia are significantly decreased at lower doses of bupivacaine administration. Thus, lower doses can be used to induce spinal anesthesia successfully with minimal adverse effects.